Analisis Faktor – Faktor Dan Perhitungan Biaya Dalam Menentukan Harga Jual Tiket. Studi Kasus Pada PT. Eka Sari Lorena Transport Bogor - ., Muanas; Nugraha, Ryan Angga (Jurnal Ilmiah Akuntansi Kesatuan, 2016)
There are two main factors in deciding ticket price in transportation providers. They are the direct and indirect costs. Other than that, there are also other external factors affecting the ticket price, which are distance, load factor, expected profit and the managerial decision to increase and/or decrease the ticket selling price. All of these components are calculated until finally come up to final ticket price. The research is conducted to analyse the factors influencing the ticket price and to find out how the ticket price is calculated. The result shows that the research object has properly calculating the ticket selling price, but still can not define a break event point. This is important if the company wishes to achieve its objectives, one of which is maximum profit. The goal in calculation of break event point is to determine the uncertain figure by managerial policy on estimated profit, load factor, and final rounding offs.